1992
DOI: 10.1116/1.578166
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic immersion ellipsometry study of the mechanism of Si/SiO2 interface annealing

Abstract: In this study we apply an interface sensitive ellipsometry technique to study the evolution of the Si–SiO2 interface as a function of high temperature annealing (750–1100 °C). Essentially, the ellipsometry technique embodies the use of liquids that refractive index match with the bulk film thereby removing the optical response of the overlayer and greatly enhancing sensitivity to the interface. According to both time and temperature of anneal, distinct modes of behavior are observed for the evolution of the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1993
1993
2001
2001

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 38 publications
(9 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…The most commonly used optical techniques are single wavelength and spectroscopic ellipsometry, 29,[70][71][72][73][74][75][76][77][78][79][80][81][82][83][84][85] reflectance difference spectroscopy ͑RDS͒, [86][87][88] second harmonic generation ͑SHG͒, [89][90][91][92][93][94][95][96][97] and Fourier transform infrared spectroscopy ͑FTIR͒. 82,98 -107 Ellipsometry is based on the measurement and subsequent modeling of changes in the polarization state of a light beam reflected from a sample surface, as is illustrated in Fig.…”
Section: A Optical Methodsmentioning
confidence: 99%
“…The most commonly used optical techniques are single wavelength and spectroscopic ellipsometry, 29,[70][71][72][73][74][75][76][77][78][79][80][81][82][83][84][85] reflectance difference spectroscopy ͑RDS͒, [86][87][88] second harmonic generation ͑SHG͒, [89][90][91][92][93][94][95][96][97] and Fourier transform infrared spectroscopy ͑FTIR͒. 82,98 -107 Ellipsometry is based on the measurement and subsequent modeling of changes in the polarization state of a light beam reflected from a sample surface, as is illustrated in Fig.…”
Section: A Optical Methodsmentioning
confidence: 99%
“…We have shown that the sensitivity is increased more than tenfold using the liquid ambient. 9 In our previous research, we investigated the evolution of the SiISiO 2 interface as a function of high temperature annealing (750-10000C) by SIE 10 and used the interface model shown in Fig. 2, which is also applicable to this study.…”
Section: Abstract (Maximum 200 Words)mentioning
confidence: 99%
“…Yakovlev et al reported on the near-interfacial properties using visible spectroscopic ellipsometry with the immersion method. 35,36 They assumed that the protrusions of silicon and the suboxide exist at the interface, and determined that the interfacial layer thickness and the volume fraction are 0.98ϩ0.34 nm and from 0.687 to 0.991, respectively, summed over oxide and suboxide. Translating their result to ours, a depolarization factor L of 0.6 using the relations aϭͱ2D/(4R) and Lϭa/(aϩ2), where the radius of protrusions, R, is 0.98 nm and the distance between protrusions D, is 4.4 nm, are obtained.…”
Section: Comparison With Other Resultsmentioning
confidence: 99%